Actual Problems of Youth Entrepreneurship at the Modern Stage - SHAYKHUTDINOVA, Gulnara Flurovna; ZHIDKOVA, Ella Vyacheslavovna; MINISHEVA, Larisa Valerievna; NIKONOVA, Svetlana Alexandrovna; SHARIPOVA, Irina Miniakhmetovna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
At the modern stage of development of market economy in Russia, the problems of youth entrepreneurship development have become more urgent. Youth, who has creative way of thinking and is inclined to running their own businesses as well as to innovation and risk, and who has the highest standard of knowledge of the Internet technologies, is a part of the society. Drawing of youth into business environment promotes to solving the employment problem in the labor market. Statistical data, given in the article, demonstrate youth concentration in wholesale and retail trade, repairs of motor transport vehicles, motorbikes, household appliances and items of personal use. The authors have considered the legislative acts, which regulate youth entrepreneurship and the infrastructure of youth entrepreneurship support in the republic of Bashkortostan. The main characteristics of a modern young entrepreneur, including professional, intellectual, organizing, leader, communicative, cultural, ethical and physical ones, have been examined. A number of measures, directed at the solution of problems of youth entrepreneurship development, have been suggested.
Keywords: youth entrepreneurship, forms of state support, infrastructure of support, a young entrepreneur, the main characteristics of a young entrepreneur